The Role of Artificial Intelligence in Talent Acquisition and Retention - Setyawan, Gogor Christstmass; Zou, Guijiao; Jie, Lie; Jixiong, Cai; Widyatiningtyas, Reviandari (Journal Markcount Finance, 2024)
Artificial intelligence (AI) is increasingly being used in various fields in the ever-growing digital era, including human resource management (HR). AI technology can solve problems such as long recruitment processes and retaining quality employees. The aim of this research is to find out how AI can improve this process. The focus of the research is how AI can be used to identify, assess and manage talent across organizations. The aim of this research is to see how AI functions in the employee acquisition and retention process. Specifically, the goal of this research is to identify how AI is used in the recruitment process to find and assess the right candidates, evaluate how effective the use of AI is in increasing employee satisfaction and engagement, and see how implementing AI impacts employee retention in the long term. Qualitative and quantitative methods were combined in a mixed approach in this research. HR managers and employees applying AI in recruitment and retention processes in various companies were thoroughly interviewed. Currently, surveys distributed to employees are used to collect quantitative data to measure employee satisfaction and engagement levels. For qualitative and quantitative data, thematic analysis and inferential techniques were used. The research results show that AI can be used in the recruitment process to reduce the time and costs required to find the right candidate. AI also helps reduce bias in candidate assessments, meaning better hiring decisions. Additionally, the use of AI in employee management increases employee satisfaction and engagement as it enables career development and work experiences tailored to them. According to survey results, employees who work with AI systems feel more valued and have better relationships with their organizations. The study found that AI significantly improves the efficiency and effectiveness of talent acquisition and retention processes. The use of AI not only speeds up and simplifies the recruitment process, but also increases employee satisfaction and their retention.